2023
DOI: 10.1186/s12864-023-09664-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug-target binding affinity prediction using message passing neural network and self supervised learning

Leiming Xia,
Lei Xu,
Shourun Pan
et al.

Abstract: Background Drug-target binding affinity (DTA) prediction is important for the rapid development of drug discovery. Compared to traditional methods, deep learning methods provide a new way for DTA prediction to achieve good performance without much knowledge of the biochemical background. However, there are still room for improvement in DTA prediction: (1) only focusing on the information of the atom leads to an incomplete representation of the molecular graph; (2) the self-supervised learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Flow forecasting is significant for planning transportation and allocating basic transportation resources [21]. In recent years, deep learning has played an essential role in computer science and other fields [22]. With the extensive application of new generational information technologies such as artificial intelligence and big data, intelligent transportation systems will become more intelligent, providing more personalized and convenient travel services for urban residents.…”
Section: Resultsmentioning
confidence: 99%
“…Flow forecasting is significant for planning transportation and allocating basic transportation resources [21]. In recent years, deep learning has played an essential role in computer science and other fields [22]. With the extensive application of new generational information technologies such as artificial intelligence and big data, intelligent transportation systems will become more intelligent, providing more personalized and convenient travel services for urban residents.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, it is imperative to delve into DTA prediction methods based on deep learning from three key perspectives: Performance analysis of multiple state-of-the-art methods based on KIBA dataset. The evaluation metric values of these methods in the figure are sourced from References (Bi et al, 2023;Xia et al, 2023;Tian et al, 2024;Wu et al, 2024;Zhou et al, 2024). Performance analysis of multiple state-of-the-art methods based on Davis dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 highlights PDBbind, KIBA, and Davis datasets as commonly used datasets for predicting DTA using deep learning. We summarized the performance evaluation metrics values of several state-of-the-art methods on PDBbind, KIBA, and Davis datasets, as reported in recently published literatures ( Wang et al, 2023a ; Zhu et al, 2023a ; Bi et al, 2023 ; Xia et al, 2023 ; Tian et al, 2024 ; Wu et al, 2024 ; Zhou et al, 2024 ), without considering the specific partitioning of the corresponding datasets by these methods. Although the statistical results ( Tables 4 , 5 ; Figures 5 – 7 ) showed that these methods have achieved good prediction performance for DTA on commonly used benchmark datasets, the further improvement in DTA prediction still faces challenges.…”
Section: Performance Analysis Of Multiple State-of-the-art Methods Ba...mentioning
confidence: 99%
See 2 more Smart Citations